Efficacy of Staple Line Reinforcement With Omentopexy During Laparoscopic Sleeve Gastrectomy on Postoperative Complications: Experience of a Single Center - Lale, Azmi; Aygen, Erhan; Kirkil, Cuneyt; Artas, Hakan; Yur, Mesut (Lippincott Williams & Wilkins, 2021)
Background: The aim of this study was to evaluate the protective effects of staple line reinforcement with omentopexy during laparoscopic sleeve gastrectomy on postoperative complications. Materials and Methods: A total of 3942 laparoscopic sleeve gastrectomy cases were included in the study. All the patients were divided into 3 groups: No reinforcement (NoSLR), staple line reinforcement with fibrin glue (SLR-FG), and staple line reinforcement with omentopexy (SLR-O). Demographic data and perioperative characteristics of the groups were analyzed retrospectively. Among these, age, sex, preoperative comorbidities, American Society of Anesthesiologists scores, body mass index, duration of operation, reoperation, complications, and Clavien-Dindo classification scores were recorded. Results: Age, sex, body mass index, comorbid diseases, American Society of Anesthesiologists, and Clavien-Dindo Classification scores were similar in all the groups. The overall complication rate was 3.0%. The overall minor and major complication rates were 1.7% and 1.3%, respectively. The mortality rate was 0.1% (4 patients). The most common postoperative complications were bleeding (0.9%) and leakage (0.5%). The incidence of leakage, bleeding, and twisted gastric sleeve rates were similar when compared between SLR-FG and NoSLR. In the SLR-O patients, the incidence of leakage, hemorrhage, and twist were significantly lower and the operation time was significantly longer when compared with the other groups. Conclusions: The SLR-O technique, especially when performed by experienced surgeons, is a promising method for the prevention of postoperative leakage, bleeding, and twist complications with an acceptable increase in the duration of operation. Considering the limited effects of the SLR-FG technique, it was predicted that it would lose its popularity over time.
Keywords: laparoscopic sleeve gastrectomy; gastropexy; omentopexy; staple line reinforcement; buttressing; fibrin glue